The Efectiveness of Using the Hangman Game in Teaching Arabic Vocabulary in Elementary Schools - Princessa Fathiyah Azoes; Asep Sopian; Nalahuddin Saleh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to evaluate the effectiveness of using the Hangman game in teaching Arabic vocabulary to fourth-grade students at Istiqomah Lembang Elementary School. Using a pretest-posttest quasi-experimental design with a control group, the experimental class received Hangman-based instruction, while the control group received conventional instruction. Statistical analysis revealed that the data were not normally distributed but homogeneous; therefore, non-parametric tests were applied. The Wilcoxon test results indicated a significant improvement in the experimental class (p = 0.007), while the Mann-Whitney test showed no significant difference between groups (p = 0.166). The average N-Gain of the experimental class was 0.4783 (moderate category), while the control class was -0.0056 (low category). These findings indicate that although the Hangman game can increase students' motivation, interest, and engagement, its effectiveness in improving vocabulary mastery remains moderate. Factors such as implementation time, classroom atmosphere, and student readiness also influence the results. This study recommends the development of a more structured and adaptive game-based learning model to improve Arabic vocabulary learning outcomes at the elementary school level.